The basics of hacking and penetration testing ethical hacking and penetration testing made easy - Engebretson, Pat (Patrick Henry) (Syngress, an imprint of Elsevier, 2013)
This book is meant to be a very gentle yet thorough guide to the world of hacking and penetration testing. It is specifically aimed at helping you master the basic steps needed to complete a hack or penetration test without overwhelming you. By the time you finish this book, you will have a solid understanding of the penetration testing process and you will be comfortable with the basic tools needed to complete the job.